Mobility and QoS aware anycast routing in Mobile ad hoc Networks. (November 2015) - Basarkod, P.I.; Manvi, S.S.
Graphical abstract: Highlights: Anycast routing is important in terms of resources, robustness and efficiency. The proposed model is based on node stability, congestion and link/route expiry time. Performs better in terms of control overheads, PDR and end-to-end delay. Abstract: Anycast is an important way of communication for Mobile Ad hoc Networks (MANETs) in terms of resources, robustness and efficiency for replicated service applications. Most of the anycast routing protocols select unstable and congested intermediate nodes, thereby causing frequent path failures and packet losses. We propose a mobility and quality of service aware anycast routing scheme in MANETs (MQAR) that employs three models: (1) node movement stability, (2) channel congestion, and (3) link/route expiry time. These models coupled with Dynamic Source Routing (DSR) protocol are used in the route discovery process to select nearest k-servers. A server among k-servers is selected based on less congestion, route expiry time, number of hops, and better stability. The simulation results indicate that proposed MQAR demonstrates, reduction in control overheads, path delays and improved packet delivery ratio compared to existing methods such as flooding, DSR and load balanced service discovery.